Pengaruh Cita Rasa, Promosi melalui Media Sosial, Store Atmosphere, dan Kualitas Pelayanan dengan Harga sebagai Variabel Intervening terhadap Keputusan Pembelian di Coffee Shop Scope Coffe Tuban - Adinda Eka Novita Sari; Hamidah Hendrarini; Prasmita Dian Wijayanti (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The Purpose of this research aims to analyze the effect of exogen latent variables taste (X1), promotion through social media (X2), store atmosphere (X3), and service quality (X4), with endogen variable namely purchase decision (Y1) and price (Z1) as an intervening variable. Place of this research was conducted in coffee shop Scope Coffe in Tubanwith a total respondents is 97 were the analyzed by Structural Equation Model Partial Least Square (SEM- PLS) with Smart PLS app 4.0 version. The result of this research is the direct effect and indirect effect, with the accepted result of direct effect is variables taste, and service quality to price variable where the p- values < 0.05 and t-statistic > 1.96, and the result of indirect effect accepted is price variable fully mediate variable service quality to purchase decision where the p- values < 0.05 and t-statistic > 1.96.